MONITORING OF MESOTHELIOMA IN SOUTHERN BRAZIL: A SITUATION TO BE INVESTIGATED - Francisco José Koller; Leila Maria Mansano Sarquis; Maria de Fátima Mantovani; Fernanda Moura D'Almeida Miranda; Dario Consonni; Carolina Mensi (Universidade Federal do Paraná, 2017)
Brazil is one of the world's greatest producers of chrysotile, but the occurrence of mesothelioma is apparently low. However, identification of cases of mesothelioma is difficult due to errors of diagnosis and registries of deaths. This is an epidemiological, descriptive and retrospective study of hospital records of Brazil's National Institute of Cancer (INCA). Records of pleural cancer or mesothelioma histology from the 2001-2014 period were selected. We identified 208 records, but only 58 cases of mesothelioma histology. Notably, 13 (22%) had been incorrectly coded as lung cancer. In half the cases, there was no registration of the latest occupations of the patients. We conclude that hospital data on mesothelioma is still imprecise and was incorrectly coded. Besides, the registries do not include information on the workplace and occupation. These findings confirm the need for a proper registry of cases of mesothelioma.